Advances in the treatment of polyarticular juvenile idiopathic arthritis. Issue 5 (September 2015) - Webb, Kate; Wedderburn, Lucy R.
<x xml:space="preserve">Abstract</x> Purpose of review To review recent advances in the management strategies of polyarticular course juvenile idiopathic arthritis (JIA) and identify unanswered questions and avenues for further research. Recent findings There is evidence for an early, aggressive, treat-to-target approach for polyarticular JIA. Clinical disease activity criteria have been recently defined and validated, including criteria for inactive disease and the juvenile arthritis disease activity score (JADAS). There is a need for evidence-based, defined disease targets and biomarkers for prediction of response, including targets for remission induction, and guidelines on drug withdrawal. Recent treatment consensus plans and guidelines are discussed and compared, including the 2015 NHS England clinical policy statement, the 2014 Childhood Arthritis and Rheumatology Research Alliance (CARRA) treatment plans and the 2011 American College of Rheumatology (ACR) guidelines. Evidence for new agents such as tocilizumab, rituximab, golimumab, ustekinumab, certolizumab and tofacitinib is promising: the recent clinical trials are summarized here. Stratification of individual patient treatment remains a goal, and predictive biomarkers have been shown to predict success in the withdrawal of methotrexate therapy. Summary There are promising advances in the treatment approaches, disease activity criteria, clinical guidelines, pharmaceutical choices and individually stratified therapy choices for polyarticular JIA.